Process intensification of distillation using a microwick technology to demonstrate separation of propane and propylene. Issue 10 (29th June 2018) - Bottenus, Danny; Caldwell, Dustin; Fischer, Christopher; Humble, Paul; Powell, Michael; Lucke, Richard; TeGrotenhuis, Ward
Abstract : Process intensification (PI) of distillation using a microchannel distillation (MCD) device successfully reduced the height of a theoretical plate (HETP) in separating propane and propylene to 1.2 cm, representing 10 theoretical stages. Mass transfer is enhanced using thin wicking structures that are 0.17 mm thick in counterflow with vapor. Liquid is segregated in the wicks by applying a siphon relative to the vapor phase, which also enables the device to operate horizontally. A scalable device containing 11 wicks was operated cryogenically in total reflux. The HETP varied between 1.2 and 4.5 cm, representing a dramatic reduction over commercial structured packings and comparable to other PI approaches. Significant improvements are expected with further development. Potential application for intensified distillation processes include distributed manufacturing and difficult separations involving close boiling compounds and meeting high purity specifications. The ultimate application is isotopic enrichment, where the number of stages required is typically multiple thousands. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3690–3699, 2018